The hidden kingdom - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire, 2014)
The five dragonets of the prophecy are hoping to hide in safety in the RainWing kingdom, and Glory is hoping to learn more about her own identity, but when tribe members start disappearing and the old queen does nothing, it is up to Glory and her friends to uncover the lurking evil.